Clinical efficacy of oligonol® supplementation on metabolism and muscle health in middle-aged and older adults: A double-blinded randomized controlled trial. (November 2022) - Peng, Li-Ning; Lin, Ming-Hsien; Lee, Huei-Fang; Hsu, Chia-Chia; Chang, Sue-Joan; Chen, Liang-Kung
Highlights: The evidence between nutrition supplement and muscle health significantly increased. A low-molecular-weight polyphenol, Oligonol®, exhibits metabolic and anti-inflammatory effect. Oligonol supplementation significantly improved physical performance and muscle mass in men. Abstract: Background: Oligonol® is a low-molecular-weight polyphenol that has biological effects on metabolism in animals. However, little is known about its roles in muscle function and muscle quality in middle-aged and older adults. Methods: 120 participants were enrolled for study based on 1:1 randomization. Participants in the intervention group were provided 200 mg oligonol® prepared as capsules, and 200 mg placebo (dextrin) was provided in control group. Results: Data from 103 participants (52 in the intervention group and 51 in the control group) were available for analysis. The mean age of all participants was 64.0 ± 8.2 years, and two-thirds of the participants were females. Baseline demographic characteristics, functional assessment, laboratory data and muscle parameters were similar between groups. Hip circumference decreased ( p  = 0.009) during the study period, and the 6-m walking speed increased ( p  = 0.001) in women in the intervention group. In contrast, 6-m walking speed, 6-min walking distance and handgrip strength were significantly improved in men in the intervention group, but increased total body fat percentage ( p  = 0.038) and decreased mid-thigh cross-muscle area (CMA) ( p  = 0.007) were observed in the control group. Compared to the control group, the 12-week interval change in the percentage of mid-thigh CMA was maintained in men in the intervention group but was significantly decreased in the control group ( p  = 0.03, 95% CI:0.002-0.05). Conclusions: Oligonol supplementation (200 mg per day) significantly improved physical performance and muscle mass in men. Further studies are needed to confirm the potential favorable effects of oligonol® supplementation.